2018
DOI: 10.1136/bjophthalmol-2018-312225
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between aqueous flare and residual visual field area in retinitis pigmentosa

Abstract: Background/aimsTo investigate the relationship between aqueous flare, visual function and macular structures in retinitis pigmentosa (RP).MethodsClinical data from 123 patients with RP (227 eyes), 35 patients with macular dystrophy (68 eyes) and 148 controls (148 eyes) were analysed. The differences in aqueous flare between clinical entities and the correlation between aqueous flare (measured with a laser flare cell meter) versus visual acuity, visual field area (Goldmann perimetry) and macular thickness (opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Our study data showed that aqueous flare values are increased in the eyes of RP patients, compared to these values in healthy individuals, and that aqueous flare values are negatively correlated with central visual function in RP patients ( 124 ). Consistent with our observation, independent groups have reported that aqueous flare values have a negative association with visual field area ( 125 ) and a positive correlation with inner retinal thickening, which occurs during retinal degeneration and remodeling, in RP patients ( 126 ). Daylight vision in the central and peripheral area is provided by cone cells; therefore, these findings suggest that inflammation may be implicated in retinal degeneration, especially in secondary cone cell death that occurs in RP.…”
Section: Retinitis Pigmentosasupporting
confidence: 91%
“…Our study data showed that aqueous flare values are increased in the eyes of RP patients, compared to these values in healthy individuals, and that aqueous flare values are negatively correlated with central visual function in RP patients ( 124 ). Consistent with our observation, independent groups have reported that aqueous flare values have a negative association with visual field area ( 125 ) and a positive correlation with inner retinal thickening, which occurs during retinal degeneration and remodeling, in RP patients ( 126 ). Daylight vision in the central and peripheral area is provided by cone cells; therefore, these findings suggest that inflammation may be implicated in retinal degeneration, especially in secondary cone cell death that occurs in RP.…”
Section: Retinitis Pigmentosasupporting
confidence: 91%
“…12 Several cross-sectional studies have assessed the association between intraocular inflammation and visual field loss in RP. Nishiguchi et al 13 reported that aqueous flare was negatively correlated with the visual field area calculated by Goldmann perimetry. We also reported that increases in aqueous flare were negatively correlated with BCVA and the MD value.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous flare is increased in patients with RP, and increased aqueous flare is correlated with worse visual function. 12 , 13 However, there have been no studies assessing the association between aqueous flare and longitudinal visual function. In the present study, we investigated the association between aqueous flare and decline of central visual function in patients with RP using the HFA 10-2 program.…”
mentioning
confidence: 99%
“…2015; Nishiguchi et al. 2019), indicating an association between inflammation and photoreceptor cell death. In the retina of rd10 mice, the levels of pro‐inflammatory cytokines and chemokines are substantially increased.…”
Section: Introductionmentioning
confidence: 99%